2021
DOI: 10.1038/s41420-021-00661-3
|View full text |Cite
|
Sign up to set email alerts
|

Type V collagen alpha 1 chain promotes the malignancy of glioblastoma through PPRC1-ESM1 axis activation and extracellular matrix remodeling

Abstract: Glioblastoma (GBM) is a fatal cancer. Existing therapies do not have significant efficacy for GBM patients. Previous studies have shown that the collagen family is involved in the regulation of the extracellular environment of cancer cells, and these conditions could become an important factor for effective treatment. Therefore, we screened various collagen types and observed that the type V collagen α1 chain (COL5A1) gene plays a pivotal role in GBM. We further examined whether the overexpression of COL5A1 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…As a representative gene of mesenchymal subtype of GBM, COL5A1 induces the malignancy of GBM via the activation of migration/invasion ability in GBM cells [39]. In addition, the elevation of COL5A1 correlates with poor survival in patients with glioma [39]. Our results showed that NOX2 promotes the elevation of COL5A1 expression in human glioma cells.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…As a representative gene of mesenchymal subtype of GBM, COL5A1 induces the malignancy of GBM via the activation of migration/invasion ability in GBM cells [39]. In addition, the elevation of COL5A1 correlates with poor survival in patients with glioma [39]. Our results showed that NOX2 promotes the elevation of COL5A1 expression in human glioma cells.…”
Section: Discussionmentioning
confidence: 57%
“…The mesenchymal subtype of GBM is associated with resistance to various chemotherapeutic agents as well as to radiotherapy, which inevitably leads to recurrence after surgical resection [36][37][38]. As a representative gene of mesenchymal subtype of GBM, COL5A1 induces the malignancy of GBM via the activation of migration/invasion ability in GBM cells [39]. In addition, the elevation of COL5A1 correlates with poor survival in patients with glioma [39].…”
Section: Discussionmentioning
confidence: 99%
“…COL5A1 (collagen type V alpha 1 chain) was found to be related to the occurrence and progression of multiple types of malignant tumors, including breast cancer and gliomas. Recent studies found COL5A1 was positively correlated with the increasing malignancy of glioblastoma through the PPRC1-ESM1 axis activation and extracellular matrix remodeling, and it may be a potential therapeutic target for glioma [ 53 - 56 ] . FAM83D (family with sequence similarity 83 member D) is a member of FAM83 family (including FAM83A, FAM83B, and FAM83D), which has been shown to have oncogenic potential recently.…”
Section: Discussionmentioning
confidence: 99%
“…The number and time of tumor formation were related to the degree of mtDNA consumption, and long-term depletion leads to the damage of mtDNA replication thus inducing the expression of early development and survival-promoting markers, including sonic hedgehog (SHH) [ 53 ]. PPARG related coactivator 1 (PPRC1), a transcription factor and regulator of mitochondrial biogenesis, may become a new therapeutic target for glioblastoma [ 54 , 55 ]. The above studies clarify the functions of these four genes in oxidative phosphorylation and the roles in tumors.…”
Section: Discussionmentioning
confidence: 99%